2001
DOI: 10.1016/s1044-0305(00)00220-8
|View full text |Cite
|
Sign up to set email alerts
|

Chiral recognition in gas-phase cyclodextrin: Amino acid complexes—Is the three point interaction still valid in the gas phase?

Abstract: The validity of the "three-point interaction" model is examined in the guest exchange reaction involving complexes of cyclodextrins and amino acids. The amino acid guest is exchanged in the gas phase in the presence of a gaseous alkyl amine. The net reaction is proton transfer between the protonated amino acid and the alkyl amine. The amino acid is lost as a neutral species. This reaction is sensitive to the chirality of the amino acid. Several amino acids are examined as well as the respective methyl esters t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
93
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 35 publications
1
93
0
3
Order By: Relevance
“…For global minimization, heating/annealing cycles were performed using consistent valence force field (CVFF) to optimize the structure of underivatized ␤-CD:amino acid complexes. The details of these methods were published previously [16,62]. To create the ternary complex with underivatized ␤-CD, the ␤-CD:amino acid complex structure was obtained through the same heating/annealing cycles.…”
Section: Molecular Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…For global minimization, heating/annealing cycles were performed using consistent valence force field (CVFF) to optimize the structure of underivatized ␤-CD:amino acid complexes. The details of these methods were published previously [16,62]. To create the ternary complex with underivatized ␤-CD, the ␤-CD:amino acid complex structure was obtained through the same heating/annealing cycles.…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…Gas-phase complexes of tri-O-methyl ␤-cyclodextrin (␤-CD*) and di-O-methyl ␤-cyclodextrin (␤-CD°) with protonated amino acids (AA) undergo exchange reactions with amines in the gas-phase [15,16]. For example, the protonated ␤-CD* -amino acid complex, [␤-CD*:AA ϩ H] ϩ , reacts with an alkyl amine to produce the protonated ␤-CD*-alkylamine complex and a neutral amino acid, which is released from the ␤-CD* cavity after proton transfer (Scheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mild ionization procedure allows the survival of their solution state structure and their presence in the gas phase seems to take place [20]-although this question is not fully settled-without the requirement that the sample be volatile and in a solvent-free environment. An important issue that has been addressed in several studies is whether the observed peaks represent actual inclusion complexes or rather electrostatic adducts [21] formed during the electrospray process.…”
mentioning
confidence: 99%
“…These results suggest that "false positives" inclusion complexes should be precluded by applying other techniques to prove the complex formation. Since then, different studies have been reported that evidenced the existence of gas-phase inclusion complexes involving methods such as collision-induced dissociation [15,18,22], blackbody induced radiation dissociation [23], heated capillary dissociation [24], and mainly by guest-exchange reactions in gas phase with a CD host sensitive to the chirality of the amino acid guest [20,25,26].…”
mentioning
confidence: 99%